Tuberculosis treatment and drug regimens - Sotgiu, Giovanni; Centis, Rosella; D'ambrosio, Lia; Migliori, Giovanni Battista (Cold Spring Harbor perspectives in medicine, 2015)
Tuberculosis is an airborne infectious disease treated with combination therapeutic regimens. Adherence to long-term antituberculosis therapy is crucial for maintaining adequate blood drug level. The emergence and spread of drug-resistant Mycobacterium tuberculosis strains are mainly favored by the inadequate medical management of the patients. The therapeutic approach for drug-resistant tuberculosis is cumbersome, because of the poor, expensive, less-effective, and toxic alternatives to the first-line drugs. New antituberculosis drugs (bedaquiline and delamanid) have been recently approved by the health authorities, but they cannot represent the definitive solution to the clinical management of drug-resistant tuberculosis forms, particularly in intermediate economy settings where the prevalence of drug resistance is high (China, India, and former Soviet Union countries). New research and development activities are urgently needed. Public health policies are required to preserve the new and old therapeutic options.